Redes, conocimientos y capacidades en el contexto de la industria del software: Análisis del caso Bahía Blanca; Network, knowledge and capabilities in the context of the software industry - José Ignacio Diez; Nadia Giannasi; Mariela Scudelati (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– In recent decades, a growing interest in the micro and meso economic foundations of competitiveness has emerged worldwide. Many authors have seek to explain this phenomenon using approaches that rely on endogenous and relational capabilities of firms. Relational capabilities are exercised in contact with other agents and allow knowledge that circulate among networks to be properly exploited. This paper analyzes this type of entrepreneurial skills and the links that exist between software companies in the city of Bahía Blanca. The method used to study this phenomenon is social network analysis or SNA.
Keywords: C45; D85; L86; 330; networks; knowledge; capabilities; software; Bahía Blanca